A method of improving contrast in illustrations of coalified fossils - Rayner, Richard J (Bernard Price Institute for Palaeontological Research, 1992)
A simple, economic method of enhancing the contrast and, therefore, improving the qual ity of certain palaeontological photographic illustrations is outlined. The technique, which involves the use of polarising filters, in no way alters the negatives or prints. In recommending this technique, it is hoped some of the confusion arising from inadequate illustrations will be removed.
Keywords: polarizing filter; fossil photography; illustrations